Environmental DNA metabarcoding provides enhanced detection of the European eel Anguilla anguilla and fish community structure in pumped river catchments. Issue 5 (30th September 2020) - Griffiths, Nathan P.; Bolland, Jonathan D.; Wright, Rosalind M.; Murphy, Leona A.; Donnelly, Robert K.; Watson, Hayley V.; Hänfling, Bernd
Abstract: The European eel Anguilla anguilla (eel hereafter) is critically endangered and has a catadromous life cycle, which means adult eels that live in pumped catchments must pass through pumps during their downstream spawning migration. Policy makers are currently lacking detailed site‐by‐site eel distribution information to estimate the overall impact of individual pumping stations on eel escapement, and as such lack the data to enable informed prioritisation of pumping station management and targeted mitigation. This study investigated whether environmental DNA (eDNA) metabarcoding can provide increased detection sensitivity for eel and fish community structure in highly regulated pumped catchments, when compared directly to current standard practice fish survey protocols (seine netting/electric fishing). Eels were detected in 14 of 17 sites (82.4%) using eDNA metabarcoding in contrast to 3 of 17 sites (17.6%) using traditional catch methods. In addition, when using eDNA monitoring, species richness was higher in 16 of 17 sites (94.1%), and site occupancy was greater than or equal to traditional methods for 23 of 26 of the fish species detected (88.5%). Although eDNA methods presented significantly higher average species richness and species site occupancy overall, eDNA and catch methods were positively correlated in terms of species richness and site occupancy. It was therefore found that eDNA metabarcoding was a high‐sensitivity method for detecting eels in pumped catchments while also increasing the detection of overall fish community structure compared to traditional catch methods. In addition, this study highlights how eDNA monitoring is especially suited to increase the detection of particular species, with traditional methods sufficient for others. This high sensitivity, coupled with the ability to sample multiple sites in a short time frame, suggests that eDNA metabarcoding workflows could be invaluable tools when prioritising pumping station management.